Orai1 Channel Inhibition Preserves Left Ventricular Systolic Function and Normal Ca 2+ Handling After Pressure Overload - Bartoli, Fiona; Bailey, Marc A.; Rode, Baptiste; Mateo, Philippe; Antigny, Fabrice; Bedouet, Kaveen; Gerbaud, Pascale; Gosain, Rajendra; Plante, Jeffrey; Norman, Katherine; Gomez, Susana; Lefebvre, Florence; et al. (Circulation (New York, N.Y.), 2020)
Orai1 is a critical ion channel subunit, best recognized as a mediator of store-operated Ca entry (SOCE) in nonexcitable cells. SOCE has recently emerged as a key contributor of cardiac hypertrophy and heart failure but the relevance of Orai1 is still unclear. To test the role of these Orai1 channels in the cardiac pathophysiology, a transgenic mouse was generated with cardiomyocyte-specific expression of an ion pore-disruptive Orai1 mutant (C-dnO1). Synthetic chemistry and channel screening strategies were used to develop 4-(2,5-dimethoxyphenyl)-N-[(pyridin-4-yl)methyl]aniline (hereafter referred to as JPIII), a small-molecule Orai1 channel inhibitor suitable for in vivo delivery. Adult mice subjected to transverse aortic constriction (TAC) developed cardiac hypertrophy and reduced ventricular function associated with increased Orai1 expression and Orai1-dependent SOCE (assessed by Mn influx). C-dnO1 mice displayed normal cardiac electromechanical function and cellular excitation-contraction coupling despite reduced Orai1-dependent SOCE. Five weeks after TAC, C-dnO1 mice were protected from systolic dysfunction (assessed by preserved left ventricular fractional shortening and ejection fraction) even if increased cardiac mass and prohypertrophic markers induction were observed. This is correlated with a protection from TAC-induced cellular Ca signaling alterations (increased SOCE, decreased [Ca ] transients amplitude and decay rate, lower SR Ca load and depressed cellular contractility) and SERCA2a downregulation in ventricular cardiomyocytes from C-dnO1 mice, associated with blunted Pyk2 signaling. There was also less fibrosis in heart sections from C-dnO1 mice after TAC. Moreover, 3 weeks treatment with JPIII following 5 weeks of TAC confirmed the translational relevance of an Orai1 inhibition strategy during hypertrophic insult. The findings suggest a key role of cardiac Orai1 channels and the potential for Orai1 channel inhibitors as inotropic therapies for maintaining contractility reserve after hypertrophic stress.